Positive Correlation between Degree of Liver Cirrhosis and N Terminal–Pro Brain Natriuretic Peptide (NT-pro-BNP) - Mario Steffanus; IDN Wibawa; I Ketut Badjra Nadha (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Background: Liver cirrhosis (LC) is a chronic disease characterized by damage of liver parenchyme with wide fibrosis and nodules formation. One of LC complications is cirrhotic cardiomyopathy (CC). CC is diagnosed when there are more than one of the following signs: diastolic dysfunction (DD), systolic dysfunction (SD), enlargement of the cardiac chamber, electrophysiology dysfunction, and increasing of natriuretic peptide such as N Terminal–Pro Brain Natriuretic Peptide (NT-proBNP). The aim of this study was to determine the correlation between degree of liver cirrhosis and increasing of the NT-proBNP.Method: Cross-sectional analytic study was performed with 72 LC patients from May 2014 to May 2015 in Sanglah General Hospital, Denpasar. Degree of liver cirrhosis was determined by child turcotte pugh (CTP) criteria and NT-proBNP was examined by electro chemiluminescence immunoassay (ECLIA) method. LC patients with other disorders which can cause the increase of NT-proBNP were excluded.  Statistical analysis used was Spearman’s correlation test.  Results: Of 72 LC patients, 79.2% were male. Patients with CTP A were 9 (12,5%), CTP B 19 (26,4%) and CTP C 44 (61,19%). Median of NT-proBNP in CTP A was 112 pg/mL, CTP B 130 pg/mL, and CTP C 315 pg/ml. There was a strong possitive correlation between degree of liver cirrhosis and NT-proBNP (r = 0.686; p = 0.000). In this study, there was also significant comparison between NT-proBNP and CTP A,B, and C (p = 0,000) and there was no significant relation between NT-proBNP and those cofounding variables (p 0.05).Conclusion: there was a strong possitive correlation between degree of LC and NT-proBNP.